Human Resource Management and the Recruitment and Process Execution of Internship Program at Nestlé Bangladesh Limited - Aurthe, Ismath Jahan (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.